Analisis Performansi Mesin Pre-Turning dengan Metode Overall Equipment Effectiveness pada PT APCB - Fajrah, Nofriani; Noviardi (Jurnal Optimasi Sistem Industri, 2018)
PT APCB is an electronics company that produces electronic device components called Narrow Shaft. The purpose of this study is to evaluate the maintenance activity in a pre-turning machine by measuring the Overall Equipment Effectiveness (OEE) level. The OEE level is obtained based on the Availability, Performance, and Quality Rate of the pre-turning machine maintenance activities. In addition, the purpose of this study is to identify the causes of the ineffectiveness of pre-turning machine maintenance activities and provide improvement suggestions for maintenance effectiveness at PT APCB. Based on the results of the calculation of the OEE value it is known that the PT APCB company still has not reached the world standard of 85%. This shows that the company still has to improve maintenance activities in the pre-turning process. The calculation of OEE value shows that the lowest OEE level in February 2016 was 48.31%, while the highest OEE level in September 2016 was 83.23%. The low performance of the pre-turning machine process was due to the ineffectiveness of maintenance activities which were caused by 14 factors. The primary causal factor with the highest value is the bar feeder problem with the highest request frequency value of 250.